Breaking the Coupling Efficiency–Bandwidth Trade‐Off in Surface Grating Couplers Using Zero‐Order Radiation. Issue 6 (5th May 2021) - Sánchez‐Postigo, Alejandro; Halir, Robert; Wangüemert‐Pérez, J. Gonzalo; Ortega‐Moñux, Alejandro; Wang, Shurui; Vachon, Martin; Schmid, Jens H.; Xu, Dan‐Xia; Cheben, Pavel; Molina‐Fernández, Íñigo
Abstract: Silicon photonics provides wafer‐scale fabrication of densely integrated photonic circuits that are enabling breakthrough applications in datacom, artificial intelligence, and healthcare. The sub‐micrometer mode size of silicon waveguides makes efficient coupling to conventional single mode fibers extremely challenging. While advanced surface grating couplers can achieve sub‐decibel coupling efficiencies, their operation relies on diffraction phenomena, which intrinsically limit the operational bandwidth. Here a novel type of surface coupler is experimentally demonstrated that overcomes the efficiency‐bandwidth limitation of conventional diffraction gratings by harnessing zero‐order radiation from a subwavelength metamaterial waveguide to a tilted silicon prism. The device achieves a coupling efficiency above 80% to an SMF‐28 fiber in a record 1‐dB bandwidth beyond 90 nm, opening new venues for highly efficient broadband fiber‐to‐chip surface coupling in silicon photonics. Abstract : A novel type of silicon photonics surface coupler is experimentally demonstrated that overcomes the coupling efficiency–bandwidth product limit of conventional diffraction gratings. By leveraging subwavelength metamaterial engineering, the device achieves a 1‐dB bandwidth broader than 90 nm and a coupling loss of 1 dB or less, yielding the highest efficiency‐bandwidth product yet reported for surface couplers.